A review on application of mobile media in personalized special education - Wang, Beili; Ramli, Saiful Hasley; Roslan, Samsilah; Abdul Rahman, Ahmad Rizal (Arts and Science Press Pte. Ltd., 2024)
Personalized special education is an educational approach that focuses on the unique needs and abilities of students with special needs, making it ideal for inclusive classrooms. Research indicates that personalized learning can enhance learning outcomes, increase engagement, and improve overall experience. Mobile media, including digital content and apps, is crucial in special education for providing inclusive experiences. These devices offer various features and functions that can be customized to meet the unique needs of students with diverse learning requirements. Benefits of using mobile media include accessibility, interactive learning, inclusive education, assistive technologies, collaborative learning, increased engagement, motivation, and feedback and assessment. Assistive technology tools like text-to-speech capabilities enhance accessibility and facilitate learning for students with diverse needs. Therefore, the behavior characteristics of special children were analyzed, and the relevant use of mobile media was obtained through literature review, which provided theoretical support for the study of mobile media design for special children through edutainment.